1998
DOI: 10.1038/bjc.1998.449
|View full text |Cite
|
Sign up to set email alerts
|

Bax expression has prognostic significance that is enhanced when combined with AgNOR counts in glottic carcinomas

Abstract: Recently. a family of genes whose encoded proteins share amino acid sequence homology with Bcl-2 have been identified. This family of proteins include Bcl-2. Bcl-x and Mcl-l. which act as blockers of apoptosis. whereas others such as Bax and Bak appear to promote apoptosis (Oltvai. 1993: Boise et al. 1995. The biological mechanisms by which the Bcl-2 gene family regulate apoptosis remain uncertain. The Bax protein seems. however. to act as a central regulator within this multigene family. Several studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

1999
1999
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 28 publications
2
23
0
1
Order By: Relevance
“…This observation concurs with the results of our previous study of glottic SCC. 19 Our study further revealed that high expression of Bcl-2 was significantly associated with poor prognosis and low expression with good prognosis. Previous studies of Bcl-2 expression in head and neck carcinomas have shown that both positive and negative tumors have been associated with good prognosis.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…This observation concurs with the results of our previous study of glottic SCC. 19 Our study further revealed that high expression of Bcl-2 was significantly associated with poor prognosis and low expression with good prognosis. Previous studies of Bcl-2 expression in head and neck carcinomas have shown that both positive and negative tumors have been associated with good prognosis.…”
Section: Discussionmentioning
confidence: 65%
“…14,16 The opposite correlation was found in prostate and testicular carcinomas, 33,34 whereas no such correlation was demonstrated in colorectal carcinomas. 35 Overexpression of the Bax protein has been associated with favorable outcome in breast adenocarcinoma and glottic SCC 18,19 and poor prognosis in ovarian carcinomas, 20 whereas no association between Bax expression and prognosis was found in a study of gastric carcinomas. 36 The contradictory results concerning prognosis and expression of Bax and Bcl-2 proteins, for tumors of the head and neck as well as tumors at other sites, indicate that induction of apoptosis by proteins of the bcl-2 gene family is very complex and that the influence of individual proteins may vary from tumor to tumor.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Der Vorhersagewert von bax wurde bei Kopf-Hals-Karzinomen bislang kaum untersucht.Aufgrund der apoptosefördernden Eigenschaften des Proteins sollte seine Expression eine eher günstige prognostische Bedeutung besitzen [14,35]. Die Daten der vorliegenden Arbeit lassen einen derartigen Zusammenhang nicht erkennen.…”
unclassified